(untitled) (Research, Society and Development, 2020)
In 2020, the World Health Organization (WHO) classified COVID-19 as a global pandemic. Since then, there is a need for new methods to facilitate the diagnosis and control of this disease. Currently, reverse transcription followed by real-time polymerase chain reaction (rRT-PCR) of respiratory samples obtained by swabs represents the gold standard in the qualitative detection of Sars-CoV-2 infection. However, this type of collection has several disadvantages, making saliva a potential tool for the diagnosis of COVID-19. Thus, the aim of this study is to evaluate, through a systematic review of current scientific literature, the applicability of saliva for the diagnosis of COVID-19 in comparison to current methods. A search was carried out in MEDLINE, SciELO, Scopus and Web of Science databases, using descriptors, strategies and pre-established criteria by two independent evaluators, followed by a manual search in the references of articles selected for full reading. The research strategies identified 476 studies and 1 study was added through manual search. After analysis, 200 articles were excluded because they were duplicated among results found in databases. With the completion of the screening process, 12 articles were included in this review. It was concluded that it is necessary to produce new studies in order to obtain even more reliable and effective data about the use of saliva in the diagnosis of COVID-19. However, studies have shown that this material can be an excellent alternative sample for the detection of SARS-CoV-2.